CoV diatom / nanocluster composite material, preparation method and application thereof, and tetracycline antibiotic concentration detection method

By using CoV diatomic/nanocluster composite materials in the Luminol-DO system, highly sensitive detection of tetracycline antibiotics is achieved, which solves the problems of cumbersome operation, high cost and slow detection speed of detection methods in the existing technology, and improves The accuracy and economy of detection are improved.

CN119351096APending Publication Date: 2025-01-24ZHEJIANG NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411460797.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing antibiotic detection methods have shortcomings in terms of operational ease, cost control and detection speed, making it difficult to achieve rapid, accurate and efficient detection of various types of antibiotics in water bodies.

Method used

The COV dual-atom/nanoplastic cluster composite material is constructed in the Luminol-DO system. The concentration of tetracycline antibiotics is detected through electrochemical chemical luminescence (ECL) analysis system to achieve high sensitivity and high selective testing.

Benefits of technology

This method can achieve highly sensitive detection of tetracycline antibiotics while simplifying the operation process and reducing costs. It has excellent stability and linear response characteristics and improves detection accuracy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351096A_ABST
    Figure CN119351096A_ABST
Patent Text Reader

Abstract

The invention provides a CoV diatom / nanocluster composite material, a preparation method and application thereof, and a tetracycline antibiotic concentration detection method. Three-dimensional porous carbon is synthesized at room temperature with NaCl as a salt template, the cobalt-vanadium co-doped composite material with the porous carbon as the substrate is synthesized through high-temperature calcination, and the composite material has the synergistic effect of CoV diatoms and VN nanoclusters, so that the material has better catalytic activity, the luminous intensity and stability can be improved in a Luminol-DO system, and the luminous efficiency is improved. The CoV diatom / nanocluster composite material can be used as an excellent ECL luminescent material, meanwhile, the material has relatively good response strength to substances with reducing functional groups, and high-sensitivity detection can be carried out on antibiotics containing the reducing functional groups by constructing a CoV diatom / nanocluster composite material Luminol-DO system. The material disclosed by the invention is stable in ECL signal, can be easily modified on the surface of an electrode, and can be applied to efficient and sensitive analysis and detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of environmental detection, and in particular to a CoV diatomic / nano cluster composite material, a preparation method and application thereof, and a tetracycline antibiotic concentration detection method. Background Art

[0002] As people's living standards continue to improve, antibiotics are widely used in human medicine, livestock, poultry and aquaculture. However, since antibiotics cannot be completely absorbed by humans or animals after taking them, a large amount of antibiotics are discharged into the environment in different forms, causing pollution. While antibiotics pollute the environment, they also lead to increased drug resistance in pathogenic microorganisms, thus posing a serious threat to the ecological environment and human health. At the same time, antibiotics may also have potential toxicity to other organisms.

[0003] It is reported that antibiotic residues have been detected in environmental media (water bodies, sediments and soil) in most countries and regions. The Action Plan for the Control of New Pollutants released in 2022 pointed out the need to strengthen the monitoring and control of antibiotics in environmental media. Among various water bodies, the concentrations of erythromycin, roxithromycin, clarithromycin, tetracycline, chlortetracycline and sulfamethoxazole are the highest in effluent water, the concentration of oxytetracycline is the highest in aquaculture water, and the concentration of norfloxacin is the highest in discharged water. Among them, the concentrations of erythromycin, roxithromycin, clarithromycin, tetracycline, chlortetracycline and sulfamethoxazole in the effluent of sewage treatment plants are as high as 2.05×10 3 ,594,42.3,1.10×10 5 , 1.10×10 3 and 4.00×10 3 ng·L -1 .

[0004] Commonly used methods for detecting antibiotics include liquid chromatography, enzyme immunoassay, etc. Although these methods have excellent performance in detection accuracy, they are insufficient in terms of ease of operation, cost control, and detection speed, which limits their application in rapid detection. Existing detection technologies still have certain defects in detecting various types of antibiotics in water bodies. Therefore, with the development of science and technology and the increasing attention paid by society to antibiotic pollution in various types of wastewater, it is urgent to develop a simple, fast, accurate, efficient and inexpensive detection method. In contrast, ECL detection technology has gradually become a powerful tool for rapid detection of pollutants due to its simplicity, speed and high cost-effectiveness.

[0005] At present, bimetallic catalysts have become a research hotspot due to their superior performance, lower cost compared to precious metal materials, simple synthesis methods, good stability, high porosity and structural adjustability. This type of electrocatalyst contains two non-precious metals. The synergistic effect between these metals will increase its intrinsic catalytic activity, thereby producing a catalytic ability of "1+1>2", improving the Faraday efficiency and reducing side effects under strong oxidizing conditions. Moreover, most non-precious metal-based bimetallic electrocatalysts obtain thermodynamic structural stability by adding non-metallic elements (such as O, S, P, N, etc.). Therefore, bimetallic electrocatalysts have rich unique properties, crystal structures and electronic states, which provides more possibilities and ideas for further improving catalytic activity. Bimetallic catalysts are widely used in ORR, OER, and HER. At the same time, researchers have also found that bimetallic catalysts with ORR and OER performance also have superior luminescence performance in the field of electrochemiluminescence, which also provides new ideas for the selection of ECL luminescent materials.

[0006] However, there are currently no bimetallic catalysts as ECL luminescent materials for detecting the concentration of tetracycline antibiotics. Summary of the invention

[0007] The purpose of the present invention is to overcome the defects of the prior art and provide a CoV diatomic / nanocluster composite material and a preparation method and application thereof, and a method for detecting the concentration of tetracycline antibiotics. The CoV diatomic / nanocluster composite material prepared by the present invention can emit high-intensity and stable light in a Luminol-DO system, and a CoV diatomic / nanocluster composite material-Luminol-DO system can be constructed to perform highly sensitive detection of tetracycline antibiotics.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a CoV diatomic / nanocluster composite material, comprising the following steps:

[0010] Dissolve sodium chloride and ammonium citrate in water, stir, add ethanol, and centrifuge to dry to obtain a precipitate;

[0011] The precipitate is calcined under an inert atmosphere, and the calcined product is washed and dried to obtain porous carbon;

[0012] The porous carbon, cobalt acetylacetonate, vanadium acetylacetonate and dicyandiamide are dissolved in ethanol, stirred and evaporated to dryness to obtain a mixture;

[0013] The mixture is calcined under an inert atmosphere, and the calcined product is etched, washed, and dried to obtain a COV diatomic / nano-cluster composite material.

[0014] Preferably, the calcining of the precipitate under an inert atmosphere specifically includes:

[0015] The precipitate is heated from room temperature to 400-500°C at a rate of 5-7°C / min under an inert atmosphere for 2-3 hours, and then heated to 600-700°C at a rate of 5-7°C / min for 2-3 hours;

[0016] And / or, calcining the mixture under an inert atmosphere specifically comprises:

[0017] The mixture is heated from room temperature to 700-800°C at a rate of 5-7°C / min and calcined for 2-3 hours under an inert atmosphere;

[0018] And / or, in the step of etching the calcined product, the etching comprises: placing the calcined product in sulfuric acid, etching at 20-25° C. for 10-15 hours, and the concentration of the sulfuric acid is 0.5-1M.

[0019] Preferably, in the step of dissolving sodium chloride and ammonium citrate in water, stirring, and then adding ethanol, the mass volume ratio of sodium chloride, ammonium citrate, water, and ethanol is (20-30) g: (9-10) g: (100-200) mL: (800-900) mL;

[0020] And / or, in the step of dissolving the porous carbon, cobalt acetylacetonate, vanadium acetylacetonate and dicyandiamide in ethanol, the mass volume ratio of the porous carbon, cobalt acetylacetonate, vanadium acetylacetonate, dicyandiamide and ethanol is (0.1-0.2) g:(0.10-0.15) g:(0.10-0.14) g:(0.4-0.5) g:(100-120) mL;

[0021] And / or, the inert atmosphere includes at least one of nitrogen, helium, neon and argon.

[0022] In a second aspect, the present invention also provides a CoV diatom / nanocluster composite material, which is prepared using the preparation method.

[0023] In a third aspect, the present invention also provides an application of the CoV diatom / nanocluster composite material in detecting tetracycline concentration.

[0024] In a fourth aspect, the present invention also provides an electrode, comprising a glassy carbon electrode and a composite material located on the glassy carbon electrode, wherein the composite material is the CoV diatom / nanocluster composite material.

[0025] In a fifth aspect, the present invention further provides a method for preparing the electrode, comprising the following steps:

[0026] adding the CoV diatomic / nanocluster composite material into water to obtain a nanocluster composite material solution;

[0027] The nanocluster composite material solution is dropped onto the surface of the glassy carbon electrode and dried to obtain an electrode.

[0028] Preferably, before dropping the nanocluster composite material solution onto the surface of the glassy carbon electrode, the surface of the glassy carbon electrode is polished with aluminum oxide having a particle size of 0.05 to 0.3 μm, and then washed with water;

[0029] And / or, in the step of adding the CoV diatomic / nanocluster composite material to water, the mass volume ratio of the CoV diatomic / nanocluster composite material to water is (0.3-0.4) mg:6 mL;

[0030] And / or, the nanocluster composite material solution is dropped onto the surface of the glassy carbon electrode, and dried at 30 to 40° C. for 20 to 30 minutes to obtain an electrode.

[0031] In a sixth aspect, the present invention further provides a method for detecting the concentration of tetracycline antibiotics, comprising the following steps:

[0032] Using the electrode as the working electrode, Ag / AgCl as the reference electrode, and a platinum electrode as the counter electrode, luminol is added to the test solution containing tetracycline as an electrolyte;

[0033] The ECL signal of the working electrode is detected by an electrochemiluminescence analysis system;

[0034] The ECL signal was used to determine the concentration of tetracycline antibiotics in the test solution.

[0035] Preferably, the scanning potential range is set to -0.8V to 0.7V and the scanning rate is set to 50 to 100mV·s during the detection of the ECL signal of the working electrode. -1 ;

[0036] And / or, the tetracycline antibiotics include at least one of tetracycline, metacycline, and doxycycline.

[0037] The CoV diatomic / nano-cluster composite material, preparation method and application thereof, and tetracycline antibiotic concentration detection method of the present invention have the following beneficial effects compared with the prior art:

[0038] The present invention adopts a simple salt bath method to synthesize a porous carbon substrate, and a CoV diatomic / nanocluster composite material is synthesized by a simple calcination method, thereby obtaining a luminescent material with high ECL luminescence efficiency and stable signal. This preparation method is not only simple to operate, but also economical and efficient. Due to the synergistic effect produced by the co-doping of Co metal and V metal, the composite material has better catalytic activity. Therefore, the ECL luminescent material prepared by the method of the present invention has a signal intensity of about 12000 under the conditions of a photomultiplier tube bias voltage of 600V and an amplification order of 3. At the same time, the system can achieve high-sensitivity detection of tetracycline antibiotics, showing excellent stability and linear response characteristics, and further improving the accuracy of detection. The present invention uses a one-step detection method, simplifies the operating process, saves time and economic costs, and the method can achieve sensitive detection of tetracycline antibiotics in a large range. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0040] Figure 1 A preparation route map of the CoV diatomic / nanocluster composite material of the present invention;

[0041] Figure 2 The catalytic mechanism diagram of the CoV diatomic / nanocluster composite material of the present invention;

[0042] Figure 3 The morphological characterization of the CoV diatomic / nanocluster composite material prepared in Example 1: (AB) SEM images of the CoV diatomic / nanocluster composite material; (C) HAADF-STEM of the CoV diatomic / nanocluster composite material; (D) AC STEM of the CoV diatomic / nanocluster composite material;

[0043] Figure 4 is the XRD pattern of the CoV diatomic / nanocluster composite material prepared in Example 1;

[0044] Figure 5 This is the XPS graph of the CoV diatomic / nanocluster composite material prepared in Example 1;

[0045] Figure 6 The ECL signal diagram of the working electrode tested according to the method in Example 3;

[0046] Figure 7The ECL signal diagram of the working electrode tested according to the method in Example 4 using luminol solutions of different antibiotics as electrolytes;

[0047] Figure 8 According to the method in Example 4, luminol solutions containing tetracycline antibiotics of different concentrations were prepared as electrolytes, and the ECL signal diagram of the working electrode tested;

[0048] Fig. 9 for Figure 8 Enlarged view of B;

[0049] Fig.10 for Figure 8 Enlarged view of D;

[0050] Fig.11 for Figure 8 Enlarged view of F. DETAILED DESCRIPTION

[0051] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0052] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0053] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values ​​within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any quoted numbers (fractions or integers) within the indicated range.

[0054] The present application embodiment provides a method for preparing a CoV diatomic / nanocluster composite material, comprising the following steps:

[0055] S1. Dissolve sodium chloride and ammonium citrate in water, stir, add ethanol, and centrifuge to obtain a precipitate;

[0056] S2, calcining the precipitate under an inert atmosphere, washing and drying the calcined product to obtain porous carbon;

[0057] S3, porous carbon, cobalt acetylacetonate, vanadium acetylacetonate and dicyandiamide are dissolved in ethanol, stirred and evaporated to dryness to obtain a mixture;

[0058] S4. calcining the mixture under an inert atmosphere, etching the calcined product, washing it, and drying it to obtain the CoV diatom / nanocluster composite material.

[0059] The preparation method of the CoV diatomic / nano-cluster composite material of the present invention uses NaCl as a salt template to synthesize three-dimensional porous carbon at room temperature, and synthesizes the CoV diatomic / nano-cluster composite material with porous carbon as a substrate and cobalt and vanadium co-doped by high-temperature calcination. The composite material of the present invention has the synergistic effect of CoV diatomic and VN nano-cluster, so that the material has better catalytic activity, can improve the intensity and stability of luminescence in the Luminol-DO system, and can be used as an excellent ECL luminescent material. At the same time, the composite material has a relatively good response intensity to substances with reducing functional groups, and can be used to construct the CoV diatomic / nano-cluster composite material-Luminol-DO system to perform highly sensitive detection of antibiotics containing reducing functional groups. The preparation method of the present invention is simple and economical, the prepared material has a stable ECL signal, is easy to be modified on the electrode surface, is close to the actual detection system, and can be applied to efficient and sensitive analysis and detection.

[0060] In some embodiments, calcining the precipitate under an inert atmosphere specifically comprises:

[0061] The precipitate is heated from room temperature to 400-500°C at a rate of 5-7°C / min under an inert atmosphere and calcined for 2-3 hours, and then heated to 600-700°C at a rate of 5-7°C / min and calcined for 2-3 hours.

[0062] In some embodiments, calcining the mixture under an inert atmosphere specifically comprises:

[0063] The mixture is heated from room temperature to 700-800° C. at a rate of 5-7° C. / min under an inert atmosphere and calcined for 2-3 hours.

[0064] In some embodiments, in the step of etching the calcined product, the etching comprises: placing the calcined product in sulfuric acid at 20-25° C. for etching for 10-15 hours.

[0065] In some embodiments, the concentration of sulfuric acid is 0.5-1M, preferably, the concentration of sulfuric acid is 0.5M.

[0066] In some embodiments, sodium chloride and ammonium citrate are dissolved in water, stirred, and then ethanol is added, wherein the mass volume ratio of sodium chloride, ammonium citrate, water, and ethanol is (20-30) g:(9-10) g:(100-200) mL:(800-900) mL.

[0067] In some embodiments, in the step of dissolving porous carbon, cobalt acetylacetonate, vanadium acetylacetonate and dicyandiamide in ethanol, the mass volume ratio of porous carbon, cobalt acetylacetonate, vanadium acetylacetonate, dicyandiamide and ethanol is (0.1-0.2) g:(0.10-0.15) g:(0.10-0.14) g:(0.4-0.5) g:(100-120) mL.

[0068] In some embodiments, the inert atmosphere includes at least one of nitrogen, helium, neon, and argon.

[0069] In some embodiments, the porous carbon, cobalt acetylacetonate, vanadium acetylacetonate and dicyandiamide are dissolved in ethanol, and in the step of stirring and evaporating to dryness, the temperature controlled by stirring and evaporating to dryness is 80-90°C.

[0070] The present invention adopts a simple salt bath method to synthesize a porous carbon substrate, and a CoV diatomic / nanocluster composite material is synthesized by a simple calcination method, thereby obtaining a luminescent material with high ECL luminescence efficiency and stable signal. This preparation method is not only simple to operate, but also economical and efficient. Due to the synergistic effect produced by the co-doping of Co metal and V metal, the composite material has better catalytic activity. Therefore, the ECL luminescent material prepared by the method of the present invention has a signal intensity of about 12000 under the conditions of a photomultiplier tube bias voltage of 600V and an amplification order of 3. At the same time, the system can achieve high-sensitivity detection of tetracycline antibiotics, showing excellent stability and linear response characteristics, and further improving the accuracy of detection. The present invention uses a one-step detection method, simplifies the operating process, saves time and economic costs, and the method can achieve sensitive detection of tetracycline antibiotics in a large range.

[0071] Based on the same inventive concept, the present invention also provides a CoV diatom / nanocluster composite material, which is prepared by the preparation method.

[0072] Based on the same inventive concept, the present invention also provides an application of the above-mentioned CoV diatom / nanocluster composite material in detecting tetracycline concentration.

[0073] Based on the same inventive concept, the present invention also provides an electrode, including a glassy carbon electrode and a composite material located on the glassy carbon electrode, wherein the composite material is the above-mentioned CoV diatom / nanocluster composite material.

[0074] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned electrode, comprising the following steps:

[0075] S1, adding the CoV diatomic / nanocluster composite material into water to obtain a nanocluster composite material solution;

[0076] S2. Add the nanocluster composite material solution dropwise onto the surface of the glassy carbon electrode and dry to obtain an electrode.

[0077] In some embodiments, before dropping the nanocluster composite material solution onto the surface of the glassy carbon electrode, the process further includes polishing the surface of the glassy carbon electrode using aluminum oxide having a particle size of 0.05 to 0.3 μm, and washing the surface with water;

[0078] In some embodiments, in the step of adding the CoV diatomic / nanocluster composite material to water, the mass volume ratio of the CoV diatomic / nanocluster composite material to water is (0.3-0.4) mg:6 mL.

[0079] In some embodiments, the nanocluster composite material solution is dropped onto the surface of the glassy carbon electrode and dried at 30-40° C. for 20-30 min to obtain an electrode.

[0080] Based on the same inventive concept, the present invention also provides a method for detecting the concentration of tetracycline antibiotics, comprising the following steps:

[0081] S1. Using the above electrode as the working electrode, Ag / AgCl as the reference electrode, and a platinum electrode as the counter electrode, luminol is added to the test solution containing tetracycline antibiotics as an electrolyte;

[0082] S2, using an electrochemiluminescence analysis system to detect the ECL signal of the working electrode;

[0083] S3. Determine the concentration of tetracycline antibiotics in the test solution using the ECL signal.

[0084] Specifically, luminol is also known as luminol, its chemical name is 3-amino-phthalhydrazide, and its chemical formula is C8H7N3O2.

[0085] In some embodiments, the tetracycline antibiotic includes at least one of tetracycline, metacycline, and doxycycline.

[0086] In some embodiments, the scanning potential range is set to -0.8V to 0.7V and the scanning rate is set to 50 to 100mV·s during the detection of the ECL signal of the working electrode. -1 .

[0087] Specifically, in the above embodiment, the working electrode, the reference electrode, the counter electrode and the electrolyte constitute a three-electrode system, and the ECL signal of the working electrode is detected by the electrochemiluminescence analysis system; the ECL signal is used to determine the concentration of tetracycline antibiotics in the test solution.

[0088] In some embodiments, a 0.1 mM luminol solution is prepared with a phosphate buffer solution of pH 7.4 as a detection solution, and the parameters of the electrochemiluminescence analysis system are set as follows: photomultiplier tube bias voltage: 600 V; amplification level: 3; scanning direction: negative; scanning rate: 100 mV·s -1 With Ag / AgCl as the reference electrode and platinum electrode as the counter electrode, the scanning potential range was adjusted to -0.8-0.7 V, the ECL signal of the working electrode was detected, and the ECL signal intensity was recorded.

[0089] In some embodiments, luminol solutions containing tetracycline antibiotics at different concentrations are prepared as test solutions, and the above steps are repeated based on the CoV diatomic / nanocluster composite material-Luminol (luminol)-DO system to perform ECL detection.

[0090] Specifically, refer to Figure 1 As shown, it is a synthetic method route map of the CoV diatomic / nanocluster composite material of the present invention, sodium chloride (NaCl) and ammonium citrate (C6H 17 N3O7) is pyrolyzed in a salt bath to obtain porous carbon (CNFs). After the porous carbon, cobalt acetylacetonate (Co(acac)3) and vanadium acetylacetonate (V(acac)3) are mixed and pyrolyzed to obtain CoV diatomic / nanocluster composite materials.

[0091] The principle of the tetracycline antibiotic concentration detection method of the present invention is as follows: Figure 2 As shown in the figure, in alkaline medium, luminol (LH) is converted into luminol anion (L - ), and then the luminol anion generates luminol anion radicals (L ·- ), under the action of CoV diatomic / nanocluster composite materials, dissolved oxygen (DO) will decompose into ROS (reactive oxygen species), and the main reactive oxygen species produced in this system is singlet oxygen ( 1 O2), the reaction between active oxygen and luminol anion radical will accelerate the excited state intermediate 3-aminophthalic acid (AP 2-*), which releases strong light in the ground state. Tetracycline antibiotics are rich in reducing functional groups, which makes tetracycline antibiotics compete with luminol for reactive oxygen, causing tetracycline antibiotics to bind to reactive oxygen first, thereby reducing the luminescence intensity. The catalytic reaction of CoV diatomic / nanocluster composite materials is used to achieve high sensitivity and high selectivity detection of tetracycline.

[0092] The following further describes the CoV diatomic / nano cluster composite material of the present application and its preparation method and application, and the tetracycline concentration detection method with specific examples. This section further describes the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0093] Example 1

[0094] The present application embodiment provides a method for preparing a CoV diatomic / nanocluster composite material, comprising the following steps:

[0095] S1. Dissolve 30 g of sodium chloride and 10 g of ammonium citrate in 150 mL of water, stir at room temperature (25°C) for 2 h, add 800 mL of anhydrous ethanol, and centrifuge to dry to obtain a precipitate;

[0096] S2, placing the precipitate in a tube furnace, heating it from room temperature (25°C) to 500°C at a rate of 5°C / min under a nitrogen atmosphere for 3 hours, then heating it to 700°C at a rate of 5°C / min for 2 hours, washing the calcined product with water and drying it to obtain porous carbon;

[0097] S3, 0.1 g of porous carbon, 0.15 g of cobalt acetylacetonate, 0.1 g of vanadium acetylacetonate and 0.4 g of dicyandiamide were dissolved in 100 mL of anhydrous ethanol, and evaporated to dryness at 80 °C with stirring to obtain a mixture;

[0098] S4. Place the mixture in a tubular furnace, heat it from room temperature to 800°C at a rate of 5°C / min under a nitrogen atmosphere and calcine it for 2 hours. Place the calcined product in 0.5M sulfuric acid, etch it at room temperature (25°C) for 12 hours, centrifuge it, wash it with water, and dry it to obtain the CoV diatomic / nanocluster composite material.

[0099] Example 2

[0100] The present invention provides a method for preparing an electrode, comprising the following steps:

[0101] S1, 0.4 mg of the CoV diatomic / nanocluster composite material prepared in Example 1 was added to 6 mL of water to obtain a nanocluster composite material solution;

[0102] S2. Polish a 5 mm diameter glassy carbon electrode on 0.3 μm and 0.05 μm aluminum oxide suede for 3 min each time. Rinse the aluminum oxide adsorbed on the electrode surface with ultrapure water each time, and then blow dry with an ear cleaning bulb for later use.

[0103] S4. Add 20 μL of the nanocluster composite material solution dropwise onto the surface of the glassy carbon electrode treated in S2, and dry it in a constant temperature oven at 37° C. for 20 min to obtain an electrode.

[0104] Example 3

[0105] This embodiment provides an ECL signal detection method for CoV diatomic / nanocluster composite materials, comprising the following steps:

[0106] S1, adding luminol to a phosphate buffer solution of pH 7.4 so that the luminol concentration is 0.1 mM, and using it as an electrolyte, using Ag / AgCl as a reference electrode, a platinum electrode as a counter electrode, and the electrode prepared in Example 2 as a working electrode;

[0107] S2. The ECL signal of the working electrode was detected using the MPI-E electrochemiluminescence analysis system produced by Xi'an Ruimai Analytical Instrument Co., Ltd. The parameters of the electrochemiluminescence analysis system were set as follows: photomultiplier tube bias voltage: 600 V; amplification level: 3; scanning direction: negative; scanning rate: 100 mV·s -1 ; Detect the ECL signal of the working electrode and record the ECL signal intensity.

[0108] Example 4

[0109] This embodiment provides a method for detecting tetracycline concentration, comprising the following steps:

[0110] S1, adding luminol to a phosphate buffer solution of pH 7.4 so that the luminol concentration is 0.1 mM, and using it as an electrolyte, using Ag / AgCl as a reference electrode, a platinum electrode as a counter electrode, and the electrode prepared in Example 2 as a working electrode;

[0111] S2. The ECL signal of the working electrode was detected using the MPI-E electrochemiluminescence analysis system produced by Xi'an Ruimai Analytical Instrument Co., Ltd. The parameters of the electrochemiluminescence analysis system were set as follows: photomultiplier tube bias voltage: 600 V; amplification level: 3; scanning direction: negative; scanning rate: 100 mV·s -1 ; Detect the ECL signal of the working electrode and record the ECL signal intensity;

[0112] S3. Prepare luminol solutions containing tetracycline antibiotics at different concentrations as electrolytes (the specific preparation method is: add luminol to a phosphate buffer solution at pH 7.4 so that the luminol concentration is 0.1 mM, and then add tetracycline antibiotics to obtain luminol solutions containing tetracycline antibiotics at different concentrations). Based on the CoV diatomic / nanocluster composite material-Luminol-DO system, set the parameters of the electrochemiluminescence analysis system to be exactly the same as step S2, and detect the ECL signal of the working electrode.

[0113] Performance Testing

[0114] Figure 3 The morphology of the CoV diatomic / nanocluster composite material prepared in Example 1 is characterized. Figure 3 A and B are SEM images of the CoV diatom / nanocluster composite materials, C is the HAADF-STEM of the CoV diatom / nanocluster composite materials, and D is the AC STEM of the CoV diatom / nanocluster composite materials.

[0115] like Figure 3 As shown, the morphology and structure of the CoV single atom / nanocluster composite material were characterized by transmission electron microscopy (TEM), and it can be clearly seen that the structure of the CoV single atom / nanocluster composite material is a carbon frame with a porous structure.

[0116] Figure 4 is the XRD pattern of the CoV diatomic / nanocluster composite material prepared in Example 1;

[0117] like Figure 4 As shown, the diffraction peak at 26.6° corresponds to the (002) crystal plane of C, and the diffraction peaks at 37.6°, 43.7° and 63.5° correspond to the (111), (200) and (220) crystal planes of VN.

[0118] Figure 5 This is the XPS graph of the CoV diatomic / nanocluster composite material prepared in Example 1;

[0119] from Figure 5 It can be seen that the characteristic element binding energy peaks of C, N, O, Co, and V appear in Figure A, which completely matches the elemental composition of the CoV single atom / nanocluster composite material, confirming the effective synthesis of the material.

[0120] Figure 6 According to the method in Example 3, the ECL signal of the working electrode is detected; Figure 6The red line a in A represents the ECL signal of the working electrode in Example 3 (i.e., the glassy carbon electrode modified by the CoV diatomic / nanocluster composite material), and the black line b represents the ECL signal of the glassy carbon electrode (not modified by the CoV diatomic / nanocluster composite material); Figure 6 B is a graph showing the change in electrochemiluminescence intensity of the working electrode and the glassy carbon electrode in Example 3 over time according to the method in Example 3.

[0121] like Figure 6 As shown in Figure A, the CoV diatomic / nanocluster composite material has good luminescence properties and a luminescence potential of 0.4V; compared with the simple bare glassy carbon electrode, the ECL intensity of the CoV diatomic / nanocluster composite material is significantly enhanced; as can be seen from Figure B, after 17 cycles of scanning, the ECL signal of the glassy carbon electrode modified with the CoV diatomic / nanocluster composite material remains stable, which shows that the luminescence intensity of this material is high and stable.

[0122] Figure 7 According to the method in Example 4, a luminol solution containing 10 μg of tetracycline antibiotics was prepared as an electrolyte (specific tetracycline antibiotics were tetracycline (TC), doxycycline (Dox), and metacycline (METC)), and the ECL signal of the working electrode (i.e., the glassy carbon electrode modified by the CoV diatomic / nanocluster composite material) was tested; at the same time, according to the method in Example 4, luminol solutions of other antibiotics were prepared as electrolytes (specific antibiotics were streptomycin sulfate (STP), kanamycin (Kan), amoxicillin (AMX), sulfamethoxazole (SMZ), sulfadimethoxine (SDM), ampicillin (AMP), lincomycin hydrochloride (LIN), pefloxacin (PEF), and enrofloxacin (ENR)), and the ECL signal of the working electrode (i.e., the glassy carbon electrode modified by the CoV diatomic / nanocluster composite material) was tested; and a luminol solution without antibiotics was used as an electrolyte (the preparation method was: adding luminol to pH 7.4 phosphate buffer solution was used to make the luminol concentration 0.1 mM as the electrolyte), and the ECL signal of the working electrode (i.e., the glassy carbon electrode modified with the CoV diatomic / nanocluster composite material) was tested as a blank control. The test results are shown in Figure 7 shown.

[0123] like Figure 7 As shown, the system based on CoV diatom / nanocluster composite material-Luminol-DO has a strong response to tetracycline antibiotics and can be used for highly sensitive detection of tetracycline antibiotics.

[0124] Figure 8According to the method in Example 4, a luminol solution containing tetracycline (TC) of different concentrations (1 ng to 1000 ng) was configured as an electrolyte to test the ECL signal of the working electrode (i.e., the glassy carbon electrode modified by the CoV diatomic / nanocluster composite material); a luminol solution containing metacycline (METC) of different concentrations (1 pg to 1000 ng) was configured as an electrolyte to test the ECL signal of the working electrode (i.e., the glassy carbon electrode modified by the CoV diatomic / nanocluster composite material); a luminol solution containing doxycycline (Dox) of different concentrations (1 ng to 1000 ng) was configured as an electrolyte to test the ECL signal of the working electrode (i.e., the glassy carbon electrode modified by the CoV diatomic / nanocluster composite material); and a luminol solution without antibiotics was used as an electrolyte (the configuration method is: adding luminol to pH 7.4 phosphate buffer solution to make the luminol concentration of 0.1mM, as the electrolyte), the ECL signal of the working electrode (i.e., the glassy carbon electrode modified by the CoV diatomic / nanocluster composite material) was tested, and the ECL signal of the control (i.e., Figure 8 Control); the test results are as follows Figure 8 shown.

[0125] Figure 8 A is the test result of using luminol solution containing different concentrations (1 ng to 1000 ng) of tetracycline (TC) as the electrolyte, and B is the relationship between the ECL signal intensity and the concentration of tetracycline (TC);

[0126] Figure 8 C in the middle is the test result of using luminol solution containing different concentrations (1 pg to 1000 ng) of metacycline (METC) as the electrolyte, and D is the relationship between the ECL signal intensity and the concentration of metacycline (METC);

[0127] Figure 8 E in the figure is the test result of using luminol solution containing different concentrations (1 ng to 1000 ng) of doxycycline (Dox) as the electrolyte, and F is the relationship between the ECL signal intensity and the concentration of doxycycline (Dox);

[0128] Fig. 9 for Figure 8 The enlarged image of B. Fig.10 for Figure 8 The enlarged image of D. Fig.11 for Figure 8 Enlarged view of F.

[0129] like Figure 8 As shown, the ECL signal intensity is 1 ng mL -1 -1000ng mL -1The ECL signal intensity decreased with the increase of tetracycline concentration (A). The logarithm of tetracycline concentration was inversely proportional to the ECL signal intensity (B). The ECL signal was 0.001 ng mL -1 -1000ng mL -1 The ECL signal intensity decreased with the increase of the concentration of methacycline within a certain range (C); and after data analysis, it was found that the logarithm of the concentration of methacycline was inversely proportional to the ECL signal intensity (D); the ECL signal intensity was 1 ng mL -1 -1000ng mL -1 The value of ECL signal intensity decreased with the increase of doxycycline concentration (E). After analyzing the data, it was found that the logarithm of doxycycline concentration was inversely proportional to the ECL signal intensity (F).

[0130] Further, luminol was added to a phosphate buffer solution at pH 7.4 so that the luminol concentration was 0.1 mM, and then tetracycline was added so that the concentrations of tetracycline were 200 ng / mL, 400 ng / mL, and 600 ng / mL, respectively, to obtain actual samples 1 to 3, respectively. According to the method in Example 4, the actual samples were used as electrolytes, and the results of testing the tetracycline concentration were shown in Table 1 below.

[0131] Table 1 - Detection results of tetracycline in actual samples

[0132]

[0133] According to the data in Table 1, the working electrode of the present invention has excellent performance in terms of recovery rate, ranging from 95.09% to 104.60%, and the relative standard deviation is less than 1.48%, which shows that the accuracy and precision of the working electrode of the present invention in tetracycline analysis are effectively guaranteed.

[0134] Further, luminol was added to a phosphate buffer solution at pH 7.4 so that the luminol concentration was 0.1 mM, and then doxycycline was added so that the concentrations of doxycycline were 100 ng / mL, 400 ng / mL, and 800 ng / mL, respectively, to obtain actual samples 4 to 6, respectively. According to the method in Example 4, the actual samples were used as electrolytes, and the results of testing the doxycycline concentration were shown in Table 2 below.

[0135] Table 2 - Detection results of doxycycline in actual samples

[0136]

[0137] According to the data in Table 2, the working electrode of the present invention has excellent performance in terms of recovery rate, ranging from 91.34% to 103.10%, and the relative standard deviation is less than 2.38%, which shows that the accuracy and precision of the working electrode of the present invention in the analysis of doxycycline are effectively guaranteed.

[0138] Further, luminol was added to a phosphate buffer solution of pH 7.4 so that the luminol concentration was 0.1 mM, and then metacycline was added so that the concentrations of metacycline were 400 ng / mL, 600 ng / mL, and 800 ng / mL, respectively, to obtain actual samples 7 to 9, respectively. According to the method in Example 4, the actual samples were used as electrolytes, and the metacycline concentrations were tested as shown in Table 3 below.

[0139] Table 3 - Detection results of metacycline in actual samples

[0140]

[0141] According to the data in Table 3, the working electrode of the present invention has excellent performance in recovery rate, ranging from 95.34% to 105.22%, and the relative standard deviation is less than 4.93%, which indicates that the accuracy and precision of the working electrode of the present invention in the analysis of metacycline are effectively guaranteed.

[0142] According to Examples 1 to 4, the highly sensitive antibiotic detection and analysis method of the CoV diatomic / nanocluster composite material of the present invention is not only applicable to actual sample detection, but also has a low detection limit, excellent selectivity and reliability. In addition, the method is easy to operate, saving time and cost.

[0143] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a CoV diatomic / nanocluster composite material, characterized in that: The following steps are involved: Dissolve sodium chloride and ammonium citrate in water, stir, add ethanol, and centrifuge to dry to obtain a precipitate; The precipitate is calcined under an inert atmosphere, and the calcined product is washed and dried to obtain porous carbon; The porous carbon, cobalt acetylacetonate, vanadium acetylacetonate and dicyandiamide are dissolved in ethanol, stirred and evaporated to dryness to obtain a mixture; The mixture is calcined under an inert atmosphere, and the calcined product is etched, washed, and dried to obtain a CoV diatom / nanocluster composite material.

2. The method for preparing the CoV diatomic / nano cluster composite material as claimed in claim 1, characterized in that: The calcining of the precipitate under an inert atmosphere specifically comprises: The precipitate is heated from room temperature to 400-500°C at a rate of 5-7°C / min under an inert atmosphere for 2-3 hours, and then heated to 600-700°C at a rate of 5-7°C / min for 2-3 hours; And / or, calcining the mixture under an inert atmosphere specifically comprises: The mixture is heated from room temperature to 700-800°C at a rate of 5-7°C / min and calcined for 2-3 hours under an inert atmosphere; And / or, in the step of etching the calcined product, the etching comprises: placing the calcined product in sulfuric acid, etching at 20-25° C. for 10-15 hours, and the concentration of the sulfuric acid is 0.5-1M.

3. The method for preparing the CoV diatomic / nano cluster composite material as claimed in claim 1, characterized in that: Dissolve sodium chloride and ammonium citrate in water, stir, and then add ethanol, wherein the mass volume ratio of sodium chloride, ammonium citrate, water, and ethanol is (20-30) g: (9-10) g: (100-200) mL: (800-900) mL; And / or, in the step of dissolving the porous carbon, cobalt acetylacetonate, vanadium acetylacetonate and dicyandiamide in ethanol, the mass volume ratio of the porous carbon, cobalt acetylacetonate, vanadium acetylacetonate, dicyandiamide and ethanol is (0.1-0.2) g:(0.10-0.15) g:(0.10-0.14) g:(0.4-0.5) g:(100-120) mL; And / or, the inert atmosphere includes at least one of nitrogen, helium, neon and argon.

4. A CoV diatomic / nanocluster composite material, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 3.

5. An application of the CoV diatomic / nano-cluster composite material as claimed in claim 4 in detecting tetracycline concentration.

6. An electrode, characterized in that: It comprises a glassy carbon electrode and a composite material located on the glassy carbon electrode, wherein the composite material is the CoV diatom / nanocluster composite material as described in claim 5.

7. The method for preparing an electrode according to claim 6, characterized in that: The following steps are involved: adding the CoV diatomic / nanocluster composite material into water to obtain a nanocluster composite material solution; The nanocluster composite material solution is dropped onto the surface of the glassy carbon electrode and dried to obtain an electrode.

8. The method for preparing an electrode according to claim 7, characterized in that: Before dropping the nanocluster composite material solution onto the surface of the glassy carbon electrode, the surface of the glassy carbon electrode is polished with aluminum oxide having a particle size of 0.05 to 0.3 μm, and then washed with water; And / or, in the step of adding the CoV diatomic / nanocluster composite material to water, the mass volume ratio of the CoV diatomic / nanocluster composite material to water is (0.3-0.4) mg:6 mL; And / or, the nanocluster composite material solution is dropped onto the surface of the glassy carbon electrode, and dried at 30 to 40° C. for 20 to 30 minutes to obtain an electrode.

9. A method for detecting the concentration of tetracycline antibiotics, characterized in that: The following steps are involved: Using the electrode described in claim 6 as a working electrode, Ag / AgCl as a reference electrode, and a platinum electrode as a counter electrode, luminol is added to a test solution containing tetracycline antibiotics as an electrolyte; The ECL signal of the working electrode is detected by an electrochemiluminescence analysis system; The ECL signal was used to determine the concentration of tetracycline antibiotics in the test solution.

10. The method for detecting the concentration of tetracycline antibiotics according to claim 9, characterized in that: During the detection of the ECL signal of the working electrode, the scanning potential range was set to -0.8 V to 0.7 V and the scanning rate was set to 50 to 100 mV·s -1 ; And / or, the tetracycline antibiotics include at least one of tetracycline, metacycline, and doxycycline.